المحددات الداخلية والاقليمية للعلاقات الامريكية المصرية (1980-2010) - اديب حميد مصطفى (Journal of College of Education, 2020)
The beginning stage of the eighties is a turning point in the Egyptian political system, as well as in the march of US-Egyptian relations, due to the developments in the political system in the Arab Republic of Egypt, and the change of the Egyptian political view after it was at the time of President Gamal Abdel Nasser heading towards the east and the former Soviet Union, In the time of President Mohamed Anwar Sadat, she became heading towards the United States of America, as President Sadat viewed all of the West and the United States of America, especially as a great power that has a great role through which Egypt can play a regional role in the region, and it has followed the same pattern President Mohamed H Sunni Mubarak, so the US-Egyptian relations were distinguished from other regional countries, but this does not mean that there are no limitations limiting these relations, especially with regard to regional relations of Egypt such as their relationship (israel) and their various regional positions in which they wanted to satisfy the American side.